Strategic learning self-efficacy, strategic decision-making style, and environment as determinants of firm growth - Jeffrey G. Covin; Alessandra Lisanti; Giovanni Latorre; Katrina M. Brownell; Patrick M. Kreiser (Journal of Innovation & Knowledge)
Strategic learning self-efficacy reflects the confidence of managers in their ability to learn from the outcomes of past strategic decisions and apply that knowledge to new decisions. This research examines the relationship between strategic learning self-efficacy and a firm's industry-adjusted sales growth rate and specifies strategic decision-making style (ranging from autocratic to participative) and environmental dynamism (ranging from stable to dynamic) as contingency factors that affect this relationship. Primary and secondary data collected from 101 manufacturing firms were used to test hypothesized relationships. Results indicate that strategic learning self-efficacy is not significantly related to firm growth as a main effect. However, strategic decision-making style and environmental dynamism were both found to negatively moderate the relationship between strategic learning self-efficacy and firm growth. Moreover, strategic learning self-efficacy, strategic decision-making style, and environmental dynamism were found to have a three-way interactive effect on firm growth. Thus, dimensions of the learning context strongly influence the degree to which strategic learning self-efficacy is associated with firm growth.